443. Comparison of Clinical Characteristics of Endemic vs. SARS-CoV-2 Coronavirus Infection in Patients Admitted to a Community Teaching Hospital. (31st December 2020) - Politis, Paula Ann; Oravec, Michael J; Hoisington, Lisa; Tan, Michael; Agarwal, Shanu; Agarwal, Shanu; England, Matthew; File, Thomas M; File, Thomas M
Abstract: Background: Endemic coronaviruses [EC] (NL63, 229E, OC43, HKU1) have been identified in humans since the 1960s. Most are associated with mild upper respiratory tract infections (RTIs) but can be associated serious disease. More recently, novel coronaviruses associated with SARS, MERS, and COVID-19 caused by SARS-CoV-2 have emerged and are often associated with serious disease and death. With this report, we compare presenting clinical characteristics and some outcomes of patients hospitalized with RTIs caused by ECs or by SARS-CoV-2 (COVID-19). Methods: Patients admitted to the Summa Health System with RTIs associated with EC were identified via multiplex PCR method (BioFire™). Patients admitted with COVID-19 were identified by real-time, reverse transcriptase-PCR method using one of several platforms. Patients were selected from two existing quality improvement registries encompassing EC and COVID-19 cases. We compared clinical characteristics and outcomes of EC patients to those of COVID-19 patients using chi-squared tests for proportions and independent samples t-tests for means. Results: Shown in Table 1. Significant differences in patient characteristics with EC vs. COVID-19 included: older age, primarily Caucasian, smoking history, requiring O2 supplementation on admission, and having chronic heart, lung, or renal disease. Significant differences in patient characteristics with COVID-19 vs. EC included: admission from extended care facility, obesity, presenting with fever, gastrointestinal symptoms and/or myalgia, presence of radiographic infiltrates, abnormal liver tests, and longer length of stay (LOS). A non-significant difference was noted in 30 day mortality rates. Coronavirus OC43 accounted for 54% of EC strains. Conclusion: There were significant differences in clinical characteristics between the two groups with EC patients more likely to have lung disease (often COPD) and requiring admission for need of O2 supplementation. COVID-19 patients were more likely to present with a febrile illness associated with pneumonia and require longer LOS (often requiring O2 supplementation later in hospitalization). Patients admitted with COVID-19 present with different clinical characteristics than those with EC with numerically higher mortality rate. Disclosures: All Authors : No reported disclosures